Effect of shade trees in cocoa agroforestry systems on cocoa microclimate and productivity - Kyereh, Dennis (2017)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of Master of Philosophy in Agroforestry,